Unveiling Curvularia tuberculata-induced leaf anomalies in Rhododendron ferrugineum: implications in cultural-ecological conservation and harnessing microbial intervention in socio-economic advancement - Dhar, Juhita; Hazra, Aishee; Patra, Riddhisha; Kumar, Varun; Subramaniyan, Vetriselvan; Kumarasamy, Vinoth; Mitra, Arup Kumar; Sayed, Amany A.; Aleya, Lotfi; El-Demerdash, Fatma M.; Almutairi, Mikhlid H.; Akash, Shopnil; et al. (Frontiers in Microbiology, 2024)
The research focuses on Rhododendron ferrugineum L., Nepal's national flower and Uttarakhand's state tree, thriving in high-altitude mountain ecosystems. A study conducted in Himachal Pradesh (Latitude: N 31° 6' 2.0088", Longitude: E 77° 10' 29.9136") identified leaf anomalies resembling rust-like manifestations in R. ferrugineum. These anomalies were traced back to the pathogenic fungus Curvularia tuberculata, marking the first documented case of its impact on R. ferrugineum in India. This discovery emphasizes the need for vigilant monitoring, disease management research, and conservation efforts to protect the cultural and ecological significance of this iconic shrub.Beyond its immediate findings, the study introduces a novel dimension to Indian flora by associating C. tuberculata with R. ferrugineum, historically linked to monocotyledonous crops.The research methodology combines traditional microscopic examination with advanced genomic sequencing and phylogenetic analysis, enhancing pathogen identification accuracy.In a broader context, this research aligns with the United Nations Sustainable Development Goals (SDGs) by highlighting the importance of environmental preservation, conservation, and sustainable management. It underscores the intricate interplay between biodiversity, cultural heritage, and the need for holistic solutions. Overall, this study calls for proactive measures to protect R. ferrugineum's cultural and ecological heritage and emphasizes the significance of interdisciplinary approaches in addressing emerging ecological threats.